2020
DOI: 10.21608/ejhc.2020.109355
|View full text |Cite
|
Sign up to set email alerts
|

Talent Management Training Programand its Effect on Leadership Effectiveness among Nurse Managers

Abstract: Background:The 21 st century marks a novelperiod in the employment landscape where the importance of the explicit value of talent as a competitive weapon rises. HR executives are frequently held liable for the successful execution of talent management programs, while it is the line managers who reallyapply this method on a day to day basis. Aim: this study aimed to measure the effect of application of talent management training program on nurse managers' leadership effectivenessDesign: aquasi-experimental rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
2
0
1
Order By: Relevance
“…Also, they knew to plan the future and align the talent' objectives with healthcare organizational objectives. This result is congruent with Elhanafy and El Hesse (2021) (40) and Abdrabou and Ghonem (2020) (34) who revealed that there was a very significant enhancement in nurse managers' practice regarding talent management in the post immediately and follow up phases rather than their pre interference phase. In addition, Venkatesh (2017) (41) found that the majority of health care providers showed good talent management behaviors after integrating the talent management framework.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Also, they knew to plan the future and align the talent' objectives with healthcare organizational objectives. This result is congruent with Elhanafy and El Hesse (2021) (40) and Abdrabou and Ghonem (2020) (34) who revealed that there was a very significant enhancement in nurse managers' practice regarding talent management in the post immediately and follow up phases rather than their pre interference phase. In addition, Venkatesh (2017) (41) found that the majority of health care providers showed good talent management behaviors after integrating the talent management framework.…”
Section: Discussionsupporting
confidence: 85%
“…This result is confirmed by Mostafa et al (2021) (33) who found that there was a highly statistical general improvement in total level of nurse managers' knowledge related to talent management throughout program phases. Equally, Abdrabou and Ghonem (2020) (34) revealed that there was a greatly significant enhancement in nurse managers' knowledge concerning talent management in the post immediately and follow up phases compared with their pre involvement phase.…”
Section: Discussionmentioning
confidence: 99%
“…These results may be due to the training program provided an opportunity for nursing managers to pay attention to the talents within their departments and motivate them to work efficiently and effectively. These results regular with, Abdrabou, El-SayedGhonem, (2020) (28) , they performed quasiexperimental research on 80 head nurses and stated that there was highly statistically significant positive correlation between total knowledge, total talent management and total leadership effectiveness among nurse managers' score throughout program phases. Omotunde, Alegbeleye (2021) (29) , detected that the findings revealed that there was a positive significant relationship between talent management practices and job performance (r = 0.58, p < 0.05).…”
Section: Discussionsupporting
confidence: 76%
“…Ingram and Glod (2016) reported in their study conducted with health institutions in Poland that TM is not applied. In two quasi‐experimental studies, preintervention, it was found that the nurse managers did not have sufficient knowledge about TM (Youssef Elhanafy & Moh Samir El Hessewi, 2021) and the training on TM had an effect on increasing the knowledge and practices of nurse managers on TM (Abdrabou & El‐SayedGhonem, 2020; Youssef Elhanafy & Moh Samir El Hessewi, 2021). Another two studies found that nurses are satisfied with TM practices, and the hospital attracts, develops, motivates, and retains talented employees through the TM process (Ahmed et al., 2019; El Dahshan et al., 2018).…”
Section: Discussionmentioning
confidence: 99%